An evaluation of the effectiveness of the information, education and communication campaign (IEC) of the Local Government Unit of Cantilan's Implementation of the Local Smoke-free ordinance - Velez, Marchie Abegail Joy O. (2018)
This study was conducted to determine how effective the information, Education and Communication Campaign materials and activities of the Local Government Unit of Cantilan, Surigao del Sur when it comes to implementing Ordinance No. 2017-07 ?An Ordinance amending Ordinance No. 04-2012 entitled ?Banning smoking in public enclosed places and business establishments in the Mun. of Cantilan, Prov. Of Surigao del Sur?. The methods that were conducted are in-depth interviews with the residents and employees of LGU-Cantilan and communication audit of the documents that were gathered from the office of the Sangguniang Bayan. In applying the Diffusion of Innovation Theory, results show that Cantilangnons already have prior knowledge about smoking and the smoking bans. However, the success of the implementation is not related to the knowledge of the residents. Documents that were gathered shows that the participation of the residents to the IEC activities that were conducted were generally low, some of the material and activities implored didn?t reach the right target audience due to no communication and miscommunication. The most common barrier to the change of behavior and attitude towards smoking of the residents is the lack of proper dissemination of information and mismatched communication strategies. Almost all of the interviewees believed that proper dissemination of information and reinforcement is lacking, respondents also believe that in order to communicate properly with the residents more IEC materials such as posters, flyers and brochures must be provided since Filipinos are visual learners.